Benefits and Costs of Transport - E.T. Verhoef; P. Nijkamp; P. Rietveld; T.R. Lakshmanan (Tinbergen Institute, 1997)
This paper discusses a number of issues centred around the evaluation of the benefits and costs of transport. It is argued that, for various reasons, transport cannot be treated as an `ordinary' economic sector, and in the paper the policy implications of a number of the sector's peculiarities are addressed. Both efficiency aspects and considerations of equity and social feasibility of policies are dealt with.
Keywords: 330; Verkehr; Verkehrsgewerbe; Kosten-Nutzen-Analyse; Externer Effekt; Verkehrspolitik; Theorie